Development of Meaningful and Fun Learning with a Gamification-Based GI Model for Primary School Students - Angelikus Nama Koten; Gaudensius Jati Lamauran Koten; Thomas Kemil Masi; Trio Erawati Siregar (Postgraduate, University of Mataram, 2025)
Meaningful learning is when students are actively and constructively involved and the role of students is dominant in every series of learning. Therefore, in order for students to truly carry out their role as the center of learning, learning must be fun and not boring. This study developed a learning design with an integration between the Group Investigation (GI) model and the Gamification approach. The purpose of the study was to produce a learning design (teaching module) on the material of grade V Elementary School in the subject of science with the topic